Management of Complicated Crown Root Fracture: A Case Report - Dr. Meera Nair; Dr. Gourav Thapak; Dr. Ashtha Arya; Dr. Mallika Rawat; Dr. Kushagar Chauhar (The Bioscan, 2025)
Traumatic dental injuries, especially crown fractures affecting anterior teeth, are commonly seen among children and young adults in India, significantly diminishing their quality of life. Conventional restorative methods for complex crown fractures, such as root canal treatments followed by composite or ceramic restorations, tend to be expensive, time-consuming, and can compromise both tooth structure and appearance. An alternative approach, fragment reattachment—when the tooth fragment is available—provides a more conservative, cost-effective, and aesthetically pleasing solution. This technique helps maintain the natural shape and function of the tooth while also supporting the psychological well-being of the patient. The report emphasizes the importance of increasing clinician awareness regarding fragment reattachment as a practical and durable option for treating anterior crown fractures.